PANDEMI COVID-19 DAN PEACEFUL RISE TIONGKOK: BELT AND ROAD INITIATIVE - Fuad Azmi; Gilang Nuralam; RMT Nurhasan Affandi; Windy Dermawan (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2020)
This paper analyzes the impact caused by the COVID-19 pandemic on the Belt and Road Initiative which is part of the Peaceful Rise policy implemented by the Chinese State by conducting literature studies using the perspective of neoliberalism as the basis for analysis. The literature we use in this research ranges from books, journals, to electronic media with qualitative and quantitative data. By considering the findings obtained, we reveal the impact of this pandemic on the factors that influence the progress of China's Peaceful Rise policy and more specifically the Belt and Road Initiative policy. The conclusion we got was that the Belt and Road Initiative, which is China's effort to apply the principle of neoliberalism, has experienced problems in allocating funds, as well as a reduction in the overall workforce.